Modelling the Effect of Housing Design Unit Contract Packaging on Mass Housing Project Team Communication Performance - Kwofie, Titus Ebenezer; Adinyira , Emmanuel; Fugar , Frank (Penerbit Universiti Sains Malaysia, 2016)
Studies exploring success on mass housing projects (MHPs) continue to cite communication ineffectiveness inherent from the unique attributes of mass housing as a major problem in the delivery. Unfortunately, these studies fail to establish the nature and extent to which the observed communication ineffectiveness is attributed to the unique characteristics displayed by MHPs. Here, this study aims at exploring the influence of the housing design unit contract packaging (HDP) features of MHPs on project team communication performance. By adopting a questionnaire survey and the use of structural equation model (SEM), the study used empirical data collected from project team leaders on mass housing project sites in Ghana to assess the communication ineffectiveness inherent in the HDP attributes. The evidence gathered from the empirical study indeed supports the hypothesis that the HDP features of MHPs significantly contribute to communication ineffectiveness related to information flow and information composition among the project team. These findings affirm the uniqueness of MHPs and suggest the need for project teams and stakeholders on mass housing to adopt communication methods, medium, strategies and management approaches that fit the mass housing project environment to engender managerial and communication efficiencies in mass housing delivery.